ENHANCING VOCABULARY THROUGH ENGLISH SONGS : A SELF-DIRECTED LEARNING EXPERIENCED FOR EFL STUDENTS - Rinda Wati Rahman; Andi Rachmawati Syarif; Citra Prasiska Puspita Tohamba (Fakultas Keguruan dan Ilmu Pendidikan, 2024)
This study explores the use of songs in self-directed learning (SDL) to enhance vocabulary acquisition among English as a Foreign Language (EFL) students. While vocabulary acquisition is essential in language learning, there is limited research on how students independently use songs outside the classroom to improve their vocabulary. This qualitative case study examines the experiences of two students from Universitas Muhammadiyah Kendari, focusing on their strategies, challenges, and perceived benefits of using songs for vocabulary development. Purposive sampling was used to select participants who had a strong interest and experience in using songs for language learning, ensuring relevant insights.Data were collected through in-depth interviews, where participants discussed their song selection process, vocabulary learning strategies, and the challenges they faced. Thematic analysis was applied to identify key themes, such as motivation, repetition, self-directed learning strategies, and challenges, including fast-paced lyrics and slang.The findings show that personal motivation plays a key role in song selection, with participants choosing songs that resonate emotionally and have clear lyrics. Repetition was vital for vocabulary retention, while self-directed strategies like looking up unfamiliar words online helped expand vocabulary. However, challenges such as fast-paced lyrics and slang required adaptations, such as slowing down songs or using supplementary resources.This study highlights the potential of songs as a tool in SDL for vocabulary acquisition, suggesting a balanced approach that integrates songs with other language learning methods. It provides practical insights for EFL educators considering the use of songs in language learning